Pengaruh Expenses retrenchment, Free Assets, dan assets Retrenchment Terhadap Corporate Turnaround - Gustina, Azira Annisa Nelya; Ratih Kusumastuti; Fitrini Mansur (Owner : Riset dan Jurnal Akuntansi, 2024)
This research examines the corporate turnaround that occurs in tourism, restaurant and hotel companies that are facing financial distress which are listed on the Indonesian stock exchange for the 2020-2022 period. This study aims to prove that expenses retrenchment, free assets, and assets retrenchment affect the success of a corporate turnaround. The entire sample used in this study was 60 samples after going through a purposive sampling sample selection process. Descriptive analysis and logistic regression analysis are the methods used in this study. The final results obtained from this research are that there is no effect of Expense Retrenchment and Free Assets on Corporate Turnaround and the effect of Asset Retrenchment on Corporate Turnaround.